A Review on Methods of Face Masks Sterilization for Reuse Owing To Crisis During COVID-19 - Pradyuman Singh Rajput; Asish Kumar Saha; Insiya Gangardiwala; Anand Vijayakumar Palur Ramakrishnan (International journal of research in pharmaceutical sciences, 2020)
The COVID-19 pandemic initially started from the Wuhan capital city of Hubei Province in the People's Republic of China had now led to a severe public health hazard across the globe, the recorded death is approximately 958 thousand globally and counting. With the enormous amount of spread of the disease, a severe crisis for Personal Protective Equipment (PPE) is being noticed across the globe. Face masks being the first line of defence for all the healthcare workers as well for the common public. It became mandatory to wear face masks before entering the patient care area. The countries who are not manufacturing it locally had to depend on other countries for the procurement. As there is a severe supply chain disruption due to the lockdown measures taken by all the countries to contain the disease, so it had become difficult to procure the face masks from the manufacturing countries. The price for these PPEs is also rising at an alarming rate with the increase in the COVID-19 cases and the huge rate of consumption by the healthcare and other sectors. Therefore, with limited resources, the hospital has to run its services. The CDC, WHO and ICMR have released several guidelines from time to time for sterilization and reuse of face masks. This article will discuss the various methods that can be utilized to sterilize the face masks and reuse of it.